Medium-term effects of Dynesys dynamic stabilization versus posterior lumbar interbody fusion for treatment of multisegmental lumbar degenerative disease. (October 2017) - Wu, Haiting; Pang, Qingjiang; Jiang, Guoqiang
Objective: To compare the medium-term clinical and radiographic outcomes of Dynesys dynamic stabilization and posterior lumbar interbody fusion (PLIF) for treatment of multisegmental lumbar degenerative disease. Methods: Fifty-seven patients with multisegmental lumbar degenerative disease underwent Dynesys stabilization (n = 26) or PLIF (n = 31) from December 2008 to February 2010. The mean follow-up period was 50.3 (range, 46–65) months. Clinical outcomes were evaluated using a visual analogue scale (VAS) and the Oswestry disability index (ODI). Radiographic evaluations included disc height and range of motion (ROM) of the operative segments and proximal adjacent segment on lumbar flexion-extension X-rays. The intervertebral disc signal change was defined by magnetic resonance imaging, and disc degeneration was classified by the Pfirrmann grade. Results: The clinical outcomes including the VAS score and ODI were significantly improved in both groups at 3 months and the final follow-up, but the difference between the two was not significant. At the final follow-up, the disc height of stabilized segments in both groups was significantly increased; the increase was more notable in the Dynesys than PLIF group. The ROM of stabilized segments at the final follow-up decreased from 6.20° to 2.76° and 6.56° to 0.00° in the Dynesys and PLIF groups, respectively. There was no distinct change in the height of the proximal adjacent segment in the two groups. The ROM of the proximal adjacent segment in both groups increased significantly at the final follow-up; the change was significantly greater in the PLIF than Dynesys group. Only one case of adjacent segment degeneration occurred in the PLIF group, and this patient underwent a second operation. Conclusions: Both Dynesys stabilization and PLIF can improve the clinical and radiographic outcomes of multisegmental lumbar degenerative disease. Compared with PLIF, Dynesys stabilization can maintain the mobility of the stabilized segments with less influence on the proximal adjacent segment and may help to prevent the occurrence of adjacent segment degeneration. Dynesys is reliable for the treatment of multisegmental lumbar degenerative disease at the medium-term follow-up.